2021
DOI: 10.2174/1567205018666211208125855
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrially-Targeted Therapeutic Strategies for Alzheimer’s Disease

Abstract: : Alzheimer's disease (AD) is an irreversible, progressive neurodegenerative disease and the most common cause of dementia among older adults. There are no effective treatments avail- able for the disease, and it is associated with great societal concern because of the substantial costs of providing care to its sufferers, whose numbers will increase as populations age. While multiple causes have been proposed to be significant contributors to the onset of sporadic AD, increased age is a unifying risk factor. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 319 publications
(267 reference statements)
0
20
0
Order By: Relevance
“…Microglial cells activated via the M1 pathway are found around amyloid plaques and neurons containing neurofibrils in AD [ 181 ]. Microglia recognizes Aβ through a number of receptor complexes, including CD14, TLR2, TLR4, α6β1 integrin, CD47, and CD36, and are capable of phagocytizing amyloid [ 182 ]. On the one hand, the accumulation of Aβ in the brain of AD patients may be associated with impaired phagocytosis of amyloid by microglia [ 183 ].…”
Section: Inflammaging and Alzheimer’s Diseasementioning
confidence: 99%
“…Microglial cells activated via the M1 pathway are found around amyloid plaques and neurons containing neurofibrils in AD [ 181 ]. Microglia recognizes Aβ through a number of receptor complexes, including CD14, TLR2, TLR4, α6β1 integrin, CD47, and CD36, and are capable of phagocytizing amyloid [ 182 ]. On the one hand, the accumulation of Aβ in the brain of AD patients may be associated with impaired phagocytosis of amyloid by microglia [ 183 ].…”
Section: Inflammaging and Alzheimer’s Diseasementioning
confidence: 99%
“…The maintenance of a functional mitochondrial population during the life of neurons is of paramount importance and involves a fine regulation of mitochondrial dynamics, maintained by the coordinated interplay between mechanisms of mitochondrial fusion and fission [77,78], biogenesis [79] and mitophagy [80] (Figure 1). Thus, it is easy to imagine how the interruption of any of these mitochondrial processes has a strong impact on cellular viability and functions, since neurons in particular, on the one hand, require an incredibly high amount of energy for neurotransmission, and on the other, they need an efficient system to eliminate damaged mitochondria (for refs, see [63]) and reduce ROS-induced death [63,81].…”
Section: The Mitochondrion: Its Dysfunctions In Admentioning
confidence: 99%
“…The Aβ peptides themselves interact with an NH 2 -derived neurotoxic Tau fragment of the human Tau40 isoform (441 amino acids) in human AD synapses in association with mitochondrial ANT, a condition that further worsens mitochondrial dysfunction by aggravating the impairment of the ANT, thus leading to a strong energy metabolism deficit [46,54,55]. Aβ peptides have also been shown to interact with mitochondrial matrix components altering mitochondrial dynamics by differentially modulating fission/fusion proteins (for refs, see [63]). Finally, the effects of Aβ aggregation can be mitigated by efficient mitochondrial proteostasis (for refs, see [63]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results showed that miR-21-5p was unregulated in AuNPs treated cells, while the effect of AuNPs treatment on hNSCs was reversed after transfection with miR-21-5p inhibitor. Differential miRNA expression may be the result of AuNPs playing a role in cells and in promoting cells against Aβ.In addition to Aβ and tau protein being involved in the initiation and progression of AD, impaired mitochondrial bioenergetics and dynamics are likely major etiological factors in AD pathogenesis(Onyango et al 2021). Several reports had demonstrated the neuroprotection effects of AuNPs in different aspects.…”
mentioning
confidence: 99%